Cultivating equality in next-gen agriculture through gender-inclusive extension: A bibliometric analysis - MUKHERJEE, SWEETY; PADARIA, RABINDRA NATH; BURMAN, RAJARSHI ROY; SHRAVANI, KOTHA; SAINI, SUSHMITA; GHOSH, BHASKAR; PUNDIR, SIMRAN (The Indian Journal of Agricultural Sciences, 2026)
The advancement of next-gen agriculture hinges on integrating cutting-edge technologies and innovative approaches to improve productivity, efficiency, and sustainability. However, achieving true progress requires dismantling traditional gender barriers and ensuring women’s active participation in agricultural decision-making, training, and resource access. The present study was carried out for a period of 1988–2023 to provide a bibliometric analysis of research on gender-inclusive extension in next-gen agriculture. The study highlighted the significant contributions of women in farming and the persistent gender disparities that impede agricultural productivity and sustainability. The findings indicated a significant emphasis on Zero Hunger (SDG 2) and Gender Equality (SDG 5), underscoring the global priority to tackle food security and gender inequality. The quantum of publications on gender-inclusive development has increased notably since 2009, peaking in 2023. Co-word analysis uncovered interconnected themes like climate change adaptation, extension services, and the integration of smallholder farmers, highlighting the multifaceted nature of gender dynamics in agriculture. Co-authorship analysis revealed substantial international collaboration, with the USA being the primary contributor. The study also provided a framework for gender-inclusive extension in next-gen agriculture based on CIPP model. By promoting gender-responsive policies, capacity building, inclusive programme design, and financial inclusion, the study advocated for a holistic approach to cultivating equality in agriculture. The findings emphasised the critical role of gender dynamics in shaping agricultural advancements and the necessity of fostering an inclusive agricultural ecosystem to address global challenges such as food security and environmental sustainability.